Evaluation of Dessert Banana (Musa spp.) Cultivars for Growth, Phenological, Yield and Yield Components at Raya Azebo Districts of Tigray Region, Northern Ethiopia - Wakuma Biratu; Haile Abebe; Haileslassie Gebremeskel (Universitas Panji Sakti, 2022)
The experiment was carried out to investigate the performance of dessert banana cultivars at Raya Azebo with the aim of selecting well adaptable and high yield banana cultivar/s. To achieve the goal of the study, the experiment was laid out in randomized complete block design and replicated thrice. From the experiment, different growth, phenological, yield, and yield-related data were collected, and analyzed using SAS software version 9.3. Dwarf Cavendish cultivar flowered earlier (549.70 days). The maximum number of days (627.20) from planting to fruit setting was recorded on Ducase Hybrid cultivar. Ducase Hybrid gave significantly the maximum bunch weight for the mother (21.04 kg) and daughter (24.53 kg) tree. The maximum number of hand bunch‑1 was recorded on Ducase Hybrid cultivar on both mother (11.31) and daughter (12.17) tree. Ducase hybrid gave significantly the maximum (357.80 qt/ha) marketable fruit yield hectare‑1on the mother tree. On the daughter tree, Ducase hybrid gave significantly the highest (392.5 qt/ha) marketable fruit yield hectare-1. The average of mother and daughter tree cropping cycle revealed that Ducase hybrid gave first ranked highest marketable fruit yield (375.15 qt/ha), but sensitive to wind. Williams‑I gave the second ranked highest (334.95 qt/ha) marketable fruit yield hectare‑1. Thus, Williams-I cultivar is recommended for the local area. Further, study on water requirements and biochemical content is crucial.